PELATIHAN PELATIHAN PENINGKATAN PEMAHAMAN LINGKUNGAN UNTUK MENCEGAH KANKER PAYUDARA PADA MASYARAKAT - Riska Septia Wahyuningtyas (JURNAL ComunitÃ Servizio : Jurnal Terkait Kegiatan Pengabdian kepada Masyarakat, terkhusus bidang Teknologi, Kewirausahaan dan Sosial Kemasyarakatan, 2022)
Abstract Breast cancer is a problem that often attacks women from adolescence to the elderly. An effective way of preventing breast cancer is knowing the early symptoms of breast cancer with the BSE Movement. If this knowledge of breast cancer is given from an early age and prevention efforts are also understood from an early age, adolescents, especially high school students, will be spared the risk of this cancer. This PKM is carried out to increase students' knowledge about breast cancer and provide students' understanding that the environment can be used to improve health to fight if there are breast cancer seeds in our bodies. Giving cancer knowledge is by inviting one of the SRIKANDI cancer foundations. This PKM conducts two main activities, namely online seminars or webinars by inviting all high schools in Jakarta and the second activity, namely providing medical equipment to cancer survivors through the SRIKANDI Cancer Foundation. The result of this PKM is to increase people's knowledge that the environment is the main thing that can affect a person's psychological condition. A green environment can promote a happy and healthy psychological state. Psychological health can affect the body's immune activity. The better a person's psychological condition, the better his immunity. The better one's immunity, the better one's defense against breast cancer cells will be. So it is necessary to increase the body's immunity in order to avoid breast cancer. Keywords: cancer, breast, environment, prevent